Politik Hukum Perekonomian Berdasarkan Pasal 33 UUD 1945 - Taufiqurrohman Syahuri (The Constitutional Court of the Republic of Indonesia, 2016)
Article 33 of the 1945 Constitution of the Republic of Indonesia regulates on National Economy and Social Welfare. Thoughts and ideas of the founding fathers in drafting that article can be traced through the study of Political Law. The study was conducted by using historical approach to explore the ideas of the framers when drafting that article. Thoughts and ideas of the framers are the object of analysis in this essay. They are among other things: first, the seriousness of the state in protecting the entire nation and the homeland based on the concept of unity in a real effort to bring about social justice; second, the concept of “Social Welfare” is intended to guarantee the welfare to the state/government and all the people; third, the framers who are committed and convinced that the ideals of social justice in the economy can achieve equitable prosperity; fourth, the framers requires that the state only do the maintenance (bestuursdaad) and process (beheersdaad), instead of proprietary (eigensdaad).